Politics and Policies of Rural Authenticity - Pospěch, Pavel; Fuglestad, Eirik Magnus; Figueiredo, Elisabete (Taylor & Francis, 2021)
In this chapter, we analyse the role played by a particular notion of authenticity in the discursive framing of the Dutch farmers' protests of late 2019 and early 2020 by the protesters and various politicians. It is our contention that the authenticity claimed by and ascribed to the protesting farmers drew legitimacy from the intimate association of authenticity with the rural identified and critiqued by Theodor Adorno in his 1973 The Jargon of Authenticity. We show how the ingrained idea of farmers as inherently authentic not only drove the remarkably sympathetic initial public response to the protests, but also facilitated their alignment with populist nationalist politics. In addition, drawing on the work of Sara Ahmed and Michael Kimmel, we argue that this same idea allowed the farmers to appeal to a rural masculinity that marked their anger and violence as justified.